EAP-Swift: An Efficient Authentication and Key Generation Mechanism for Resource Constrained WSNs - Daniel Granlund; Christer Åhlund; Patrik Holmlund (International Journal of Distributed Sensor Networks)
Technological advances within the area of wireless sensor technology allow WSNs to be used in a increasing number of measurement scenarios. As new application areas are emerging, such as infrastructure monitoring and smart cities, the need for sensor mobility handling requires efficient and secure authentication protocols. This paper presents EAP-Swift, a novel EAP based authentication protocol with a focus on lightweight processing and faster response. It supports end-to-end session encryption key generation and mutual authentication. By utilizing lightweight hashing algorithms, the challenge-response authentication mechanism uses only two round trips to the AAA server for the complete authentication procedure leading to the reduction of latency by 33% compared to the baseline protocols. Further, using extensive experimentation, we validate that the authentication time can be kept below 250 ms and the power consumption can be kept below 15 mJ. Furthermore, we show that a battery lifetime of more than four years can be achieved when running the system on a regular button cell battery. Finally, the protocol was verified in terms of security using the AVISPA tool.